Comparative evaluation of ion-exchange resins for natural organic matter removal from power plant source waters - Tseka, Tebogo; Finkbeiner, Pascal; Phiri, Zebron; Nkambule, Thabo TI; Jarvis, Peter; De Kock, Lueta-Ann (Elsevier, 2025)
Natural organic matter (NOM) in source waters presents significant operational challenges for thermal power generation, including membrane fouling, scaling, and the formation of disinfection byproducts (DBPs). This study evaluated the performance of three macroporous strong-base anion exchange (IEX) resins, polyacrylic (A860S), polystyrenic (A502PS), and a polystyrene-polyacrylic blend (MPR1000), for dissolved organic carbon (DOC) removal from two industrial water sources: Vaal River raw water (Vaal RW) and Medupi ultrafiltrate (Medupi UF). Batch experiments and kinetic modelling revealed that the pseudo-second-order model best described the adsorption behaviour, indicating chemisorption as the dominant removal mechanism. Despite having the lowest ion-exchange capacity, MPR1000 achieved the highest DOC uptake in Medupi UF (47.4 ± 3.2%), while A860S demonstrated the most consistent performance across both matrices (up to 77.3 ± 4.2% in Vaal RW). In contrast, A502PS exhibited limited effectiveness due to diffusional constraints. Intraparticle diffusion analysis confirmed multi-stage mass transfer, and liquid chromatography-organic carbon detection showed preferential removal of humic substances and building blocks, with minimal uptake of low molecular weight acids and neutrals. Variations in removal efficiency were attributed not to the molecular weight of NOM but to differences in aromaticity (SUVA254) and anionic composition, particularly the sulphate content. These findings underscore the importance of aligning resin matrix characteristics with specific water chemistries to optimise IEX performance for industrial water treatment, particularly under sulphate-rich conditions common in power plant operations.
Keywords: 4004 Chemical Engineering; 40 Engineering; 4011 Environmental Engineering; 4005 Civil engineering; Natural organic matter; Ion exchange; Dissolved organic carbon; LC-OCD; Thermal power generation; SUVA; Adsorption kinetics